Inhibition of prolyl hydroxylase 3 ameliorates cardiac dysfunction in diabetic cardiomyopathy. (5th March 2015) - Xia, Yanfei; Gong, Luwei; Liu, Hui; Luo, Beibei; Li, Bo; Li, Rui; Li, Beibei; Lv, Mei; Pan, Jinyu; An, Fengshuang
Highlights: PHD3 gene silencing ameliorated diabetic cardiomyopathy via alleviating cardiac apoptosis and fibrosis. ROS mediated high glucose-induced PHD3 overexpression. PHD3 gene silencing reduced high glucose-induced H9c2 cardiomyoblasts apoptosis. MAPKs activation was involved in PHD3 mediated H9c2 cardiomyoblasts apoptosis. Abstract: Prolyl hydroxylase 3 (PHD3) is a member of the prolyl hydroxylases (PHDs) family and is induced by hypoxia. It plays a critical role in regulating the abundance of hypoxia-inducible factor (HIF). Its expression is increased in diabetic rat hearts; however, its role remains unclear. We investigated the potential role and mechanism of action of PHD3 in the setting of diabetes-induced myocardial dysfunction in rats. In vivo, type 2 diabetic rat model was induced via a high-fat diet and intraperitoneal injection of streptozotocin. PHD3 expression was knocked down using lentivirus-mediated short-hairpin RNA (shRNA). In vitro, primary neonatal cardiomyocytes and H9c2 cardiomyoblasts were cultured in 33.3 mM glucose (high glucose, HG) and 5.5 mM glucose (normal glucose, NG), the latter of which was used as a control. PHD3-siRNA was used to inhibit the expression of PHD3 and to investigate the role of PHD3 in HG-induced apoptosis in H9c2 cardiomyoblasts. Rats with diabetic cardiomyopathy (DCM) exhibited severe left ventricular dysfunction as well as myocardial apoptosis and fibrosis. PHD3 expression was increased in the myocardial tissues of diabetic rats, and inhibition of PHD3 ameliorated the disease. Additionally, the inhibition of PHD3 significantly decreased HG-induced apoptosis and MAPK activation in H9c2 cardiomyoblasts. Our results suggest that PHD3 inhibition ameliorates myocardial dysfunction in the setting of diabetic cardiomyopathy.